Workshop 7 report: The "uberisation" of public transport and mobility as a service (MaaS): Implications for future mainstream public transport. (September 2018) - Mulley, Corinne; Kronsell, Annica
Abstract: This paper synthesizes evidence from Workshop 7 'The "uberisation" of public transport and mobility as a service (MaaS): implications for future mainstream public transport' of the 15th International Conference on Competition and Ownership in Land Passenger Transport. Workshop 7 was specifically concerned with the way in which the widespread adoption of portable and/or wearable internet-connected devices such as smartphones has opened up new possibilities in the transport sector. These are referred to as 'uberisation' by some and the creation of Mobility as a Service (MaaS) by others. In some cities and countries, these new services have been welcomed and even facilitated, while in others there have been clashes with regulators as well as with incumbent operators. Workshop 7 considered how these new services might be integrated into the market and whether more widespread development of ride-hailing or ride-sharing might lead to new ways of creating flexible and truly on-demand urban bus services, or alternatively would the way public transport is organized and financed ultimately be disrupted so that what is viable in terms of competition, contracts and governance would need to be reconsidered. The Workshop presented evidence and undertook discussion that could be considered under four themes: conceptual; the role of MaaS in the uncertain future, including the new digital era; the experience of flexible transport in developing countries as compared to Australia and finally, how MaaS might provide for community needs. Over and above the detail provided by the evidence in papers, the Workshop discussion identified a tension between policy formulation and operator viewpoints, the need for flexibility in developing contracts, the importance of partnership in developing MaaS packages, including bundling mobility with other services provided by government and a need to address consumer protection issues. The Workshop developed a long list of areas worthy of further research including understanding how to move travel behaviour from ownership to mobility as a service, a need for further pilots to develop the evidence base, defining the regulatory frameworks and understanding pricing strategies.